Ethics Expertise History, Contemporary Perspectives, and Applications - Rasmussen, Lisa (Philosophy and Medicine,, 2005)
The complexity of the modern world has led to increasing professional specialization. Experts in a variety of fields, including ethics, offer advice and solutions. But where professional expertise often involves mastering certain facts, ethics expertise is distinct. It is not clear, for example, whether moral expertise consists of knowledge of right and wrong, the ability to articulate implications of moral premises, or the display of an outstanding character oneself. This volume examines philosophical conceptions of ethics expertise from both historical and contemporary perspectives, including applications of ethics expertise in such areas as bioethics consultation, expert witnessing and policy making. It will be of interest to scholars of moral philosophy as well as contemporary practitioners in many areas of bioethics.